MEDIA WARAGA SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN SISWA SEKOLAH DASAR DALAM MENGIDENTIFIKASI KERAGAMAN BUDAYA - Saktia Alifa; Imaniar Purbasari; Ristiyani Ristiyani (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This research aims to describe the enhancement of elementary school students ' ability to identify cultural diversity, as well as describe the improvement of basic skills teaching teachers through the application of Waraga media.The research method used is a class action research conducted as many as 2 cycles. Each cycle is implemented during 2 meetings. Cycles consist of planning, acting, observing, and reflecting. The subject of the study was 28 graders of SD Negeri 2 Pecangaan Wetan in Lesson 2019/2020. The technique of data collection during the implementation of class action research using test techniques in the form of evaluation test to know the improvement of students ' ability to identify cultural diversity, and nontest technique in the form of observation of teacher teaching basic skills using observation sheet consisting of 8 observed aspects. Data analysis used is quantitative and qualitative data analysis. The results showed that with the use of the media waraga in learning occurs increase the ability of students in identifying cultural diversity in elementary schools. Proven from the increasing percentage of the classical dictancy. Cycle I gained a percentage of 68% and cycle II gained 86%. The results also showed improved teacher teaching basic skills, proven from observations that gained a score percentage of 77.3% on the I cycle and increased to 85% in cycle II.